2016
DOI: 10.1155/2016/2670912
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Implementation of New WHO Diagnostic Criteria for Gestational Diabetes Mellitus on Prevalence and Perinatal Outcomes: A Population-Based Study

Abstract: Objectives. To determine the impact of the implementation of new WHO diagnostic criteria for gestational diabetes mellitus (GDM) on prevalence, predictors, and perinatal outcomes in Croatian population. Methods. A cross-sectional study was performed using data from medical birth certificates collected in 2010 and 2014. Data collected include age, height, and weight before and at the end of pregnancy, while perinatal outcome was assessed by onset of labor, mode of delivery, and Apgar score. Results. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 24 publications
(22 reference statements)
2
20
0
3
Order By: Relevance
“…Further, according to our study findings the primiparous women with GDM had more large‐for‐gestational‐age newborns than did the women without GDM. This finding is in line with several previous study findings .…”
Section: Discussionsupporting
confidence: 94%
“…Further, according to our study findings the primiparous women with GDM had more large‐for‐gestational‐age newborns than did the women without GDM. This finding is in line with several previous study findings .…”
Section: Discussionsupporting
confidence: 94%
“…In many countries the prevalence of GDM is rising [14][15][16]. Some of this is due to the increasing age at which women are becoming pregnant, an increase in obesity amongst women, more testing during pregnancy, and better recording during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a significant increase in prevalence of GDM after the introduction of the new IADPSG criteria [15,16], some pre-post studies suggest negligible clinical improvement in the adverse outcomes measured [17,18]. Findings from a qualitative study of 19 women of different cultural backgrounds investigating women's experiences of a GDM diagnosis reported that the diagnostic criteria itself was viewed as 'confusing' by some women and treatment for their 'borderline' condition unnecessary [19].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the new diagnostic criteria, the number of GDM cases detected in our cohort reduced 2.9%. Nonetheless, most studies reported an increase in the number of GDM cases [15][16][17][18][19][20] , although some studies reported similar or decreased in number of GDM cases. 21,22 This reduction reflected that most GDM cases detected in the Chinese population was by the 2HG test.…”
Section: Discussionmentioning
confidence: 98%